The Determinants of the Existing Conditions on the Functional and Spatial Development of Rural Areas - Borucińska-Bieńkowska, Hanna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article discusses selected issues regarding the influence of ecophysiographic and cultural- historical determinants on functional-spatial development of rural areas. Ecological, economic and social processes the have been past few decades are examined in the context of the development of local self-governments and the rise of free market economy after Poland`s socio-economic transformation. The process of intensive rural urbanization occurs especially in areas within the impact zone of big cities.
Keywords: ecophysiographic determinants; cultural-historical determinants; rural areas; ecological processes; social processes; uwarunkowania ekofizjograficzne; uwarunkowania kulturowo-historyczne; obszary wiejskie; procesy ekologiczne; procesy społeczne